First trimester maternal upper arm circumference correlated to placental size and neonatal anthropometry (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND First maternal nutrition, represented by anthropometrics, is an important factor for fetal growth. This study aimed to determine the correlation between maternal nutritional status of first trimester pregnant women with placental size and neonatal anthropometry. METHODS A retrospective cohort study (N = 134) was conducted in Jakarta and Riau during AugustâSeptember 2017. Correlation between first trimester maternal nutritional status, placental size (placental weight and volume), and neonatal anthropometry (birth weight, birth length, head circumference, and abdominal circumference) were examined using Spearman correlation test. RESULTS High maternal body mass index and upper arm circumference (UAC) are weakly correlated with high birth weight (r = 0.281, p<0.001 and r = 0.271, p<0.001), birth length (r = 0.176, p = 0.022 and r= 0.238, p = 0.002), head circumference (r = 0.251, p = 0.001 and r = 0.297, p<0.001), abdominal circumference (r = 0.227, p = 0.003 and r = 0.226, p = 0.003), placental weight (r = 0.198, p = 0.01 and r = 0.228, p<0.001), and placental volume (r = 0.194, p = 0.01 and r = 0.203, p = 0.008). In addition, high maternal height is also weakly correlated with high birth weight (r = 0.157, p = 0.043) and birth length (r = 0.158, p = 0.041). CONCLUSIONS UAC can be reliably used to assess the nutritional status of pregnant women and to predict placental and newborn sizes.